(untitled) (Al-Aasar, 2025)
This study examines the Qur’ānic references to the date palm (al-nakhl) by analyzing the interpretations of the early classical exegetes without incorporating contemporary scholarly opinions or the author’s personal views. The research traces the thematic evolution of exegetical insights from the earliest mufassirūn to later classical scholars, highlighting how each generation added new dimensions to the understanding of these verses. The study identifies major thematic areas, including the date palm as a sign of divine creation and a proof of the Creator, its relationship with natural laws, its spiritual symbolism, and its role as a manifestation of divine blessing, beauty, sustenance, and moral instruction. By synthesizing dispersed classical insights into an organized thematic framework, this research contributes to filling a gap in Qur’ānic botanical studies and provides a foundation for future interdisciplinary work on the natural symbols of the Qur’ān.